Mass and enthalpy budget evolution during the surge of a polythermal glacier: a test of theory. Issue 253 (29th August 2019) - Benn, Douglas I.; Jones, Robert L.; Luckman, Adrian; Fürst, Johannes J.; Hewitt, Ian; Sommer, Christian
Abstract: Analysis of a recent surge of Morsnevbreen, Svalbard, is used to test predictions of the enthalpy balance theory of surging. High-resolution time series of velocities, ice thickness and crevasse distribution allow key elements of the enthalpy (internal energy) budget to be quantified for different stages of the surge cycle. During quiescence (1936–1990), velocities were very low, and geothermal heat slowly built-up enthalpy at the bed. Measurable mass transfer and frictional heating began in 1990–2010, then positive frictional heating-velocity feedbacks caused gradual acceleration from 2010 to 2015. Rapid acceleration occurred in summer 2016, when extensive crevassing and positive air temperatures allowed significant surface to bed drainage. The surge front reached the terminus in October 2016, coincident with a drop in velocities. Ice plumes in the fjord are interpreted as discharge of large volumes of supercooled water from the bed. Surge termination was prolonged, however, indicating persistence of an inefficient drainage system. The observations closely match predictions of the theory, particularly build-up of enthalpy from geothermal and frictional heat, and surface meltwater, and the concomitant changes in ice-surface elevation and velocity. Additional characteristics of the surge reflect spatial processes not represented in the model, but can be explained with respect to enthalpy gradients.